Perbandingan Hasil Belajar Siswa Melalui Penggunaan Media Poster Berbasis PPt Interaktif dan Media Video Animasi pada Muatan IPS Kelas IV di SDN Bunulrejo 02 Malang - Yesita Galatia Maysella; Nihayati Nihayati; Syaiful Imam (Universitas Negeri Malang, 2021)
Abstract: This research was conducted with the aim of comparing the learning outcomes between students using PowerPoint-based poster learning media with animated video media in social studies subject class IV material